Composição química e avaliação antimalárica in vitro de extratos e substâncias de Andropogon leucostachyus Kunth (Poaceae) - (:unkn) unknown (Universidade Federal do Amazonas, 2017)
The absence of new drugs and the emerging parasites resistance to conventional antimalarials stimulate the search for new substances for the treatment of malaria. In order to obtain new antimalarial substances, the research group Laboratory of Active Principles of the Amazon (LAPAAM) study several medicinal plants of the Amazon, demonstrating previously that extracts of Andropogon leucostachyus Kunth have good antimalarial activity in vitro and in vivo in rodent model, however, the active substances were not determined Responsible for such activity. Thus, the present work aimed to isolate, purify, identify and / or elucidate the structures of substances present in A. leucostachyus Kunth and to evaluate them in in vitro assays against K1 Plasmodium falciparum chloroquine-resistant to determine their respective activities Antimalarial drugs. For this, extracts were prepared with hexane and ethyl acetate, which were submitted to chromatographic techniques for substance isolation and antimalarial evaluation. The determination of the chemical structures was possible by spectroscopic techniques of nuclear magnetic resonance (NMR) 1D and 2D and high resolution mass spectrometry (HRMS). From the hexane extracts of shoot and root were isolated two steroids in mixture, stigmasterol and sitosterol, and from ethyl acetate extract was isolated a phenylpropanoid, (E)-3-(2,3,6-trimethoxyphenyl) acrylic acid. The mixture of stigmasterol and sitosterol was inactive in the antimalarial assay, while (E)-3-(2,3,6- trimethoxyphenyl) acrylic acid was active in the initial screening, inhibiting parasite growth by 82,5% in the concentration of 50 μg/mL, however inactive at inhibitory concentration (IC50), with a value of 13,5μg/mL or 57 μmol.
Keywords: Produtos naturais; Antimaláricos; Sitosterol; Estigmasterol; Princípios Ativos da Amazônia; Plantas medicinais; CIÊNCIAS DA SAÚDE: FARMÁCIA